Prevalence and determinants of postpartum depression among postpartum mothers - Pariyar, Jewan; Lamichhane, Bigyan; Bhattarai, Tribhuwan; Sah, Sunil Kumar; Agrahari, Mahendra; Bhattarai, Pratik; Paudel, Yubraj; Koirala, Anil (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Postpartum depression is one of the major public health issues in developing country like Nepal, where it is often underappreciated and consequently affecting health of both mother and baby. It is mainly mood disorder causing anxiety, sadness and exhaustion, linked to maternal suicide and infanticide in developing countries. Hence this study aims to determine prevalence and determinants of postpartum depression. Method: A descriptive prospective cross-sectional study was carried out in Bharatpur Hospital from December 15 2021 to December 14 2022, among a total of 292 postpartum mothers selected through non probability sampling technique. Validated Nepalese version of EPDS was used to screen depressive symptoms and data was collected after receiving an ethical approval letter. Data entry was done using SPSS version 20. Result: Out of total postpartum mothers, prevalence of postpartum depression with EPDS score ≥13 was 41(14%). Most of the postpartum mothers enrolled in this study belonged to age group 20-30 years 219(75%) and majority of participants were Hindu by religion 246(84.2%). Brahmin / Chhetri were the commonest ethnicity 160(54.8%) and more than half i.e., 157(53.8%) had at least secondary level education, however, 148(50.7%) were housewife by occupation. Conclusion: Postpartum depression in Nepalese mothers can be detected with use of EPDS, a psychological evaluation tool. This study discovered that anxiety of labour was significant factor in development of depression and postpartum depression is most common in 20–30years age group. Policies pertaining to community, public health and medical facilities should give priority to this problem.